Pyrrolidine-fused chlorin photosensitizer immobilized on solid supports for the photoinactivation of Gram negative bacteria - Mesquita, Mariana Q.
The emergence of resistant microorganism to conventional therapeutics prompted us to search new and better antimicrobial treatment modalities. In this work was envisaged an economically viable and environmental friendly approach to allow successive recovery and removal of the photosensitizer agent after photodynamic treatment. The photodynamic inactivation of bioluminescent Escherichia coli in the presence of an immobilized cationic chlorin photosensitizer and its reusability are described. The chlorin photosensitizer (PS) was immobilized on two commercial materials: a 3-bromopropyl-functionalized silica and a Merrifield resin. The new photosensitising materials were characterized by UV-vis spectroscopy, SEM and EDX. Their singlet oxygen generation capacities were also assessed. Previous studies showed that there is a direct relationship between the photoinactivation efficiency and the number of positive charges on such PS molecules. Therefore the number of positive charges on the new prepared materials was further increased by treatment of the PS-immobilized materials with 1-methylimidazole and pyridine. The efficiency of photoinactivation against bioluminescent E. coli was evaluated in the presence of the non-immobilized chlorin (20 mu M) as well as in the presence of the new prepared materials positively charged or non-charged on the surface (20-200 mu M) with white light at an irradiance of 4.0 mW cm(-2). Overall, this study shows that the materials resulting from the immobilization of the chlorin on the silica surface and on the Merrifield resin, followed by further treatment with pyridine, have high potential as PS for the inactivation of Gram negative bacteria (3.0 log reductions) and are able to maintain its antimicrobial efficiency after at least 3 repeated cycles of photoinactivation. Their reusability, without loss of effectiveness, confirms a potential inexpensive and friendly application in clinic and environmental areas. (C) 2014 Elsevier Ltd. All rights reserved.